Preoperative anemia and associated factors in women undergoing cesarean section at a comprehensive specialized referral hospital in Ethiopia - Hassen, Alemayehu Eshetu; Agegnehu, Abatneh Feleke; Admass, Biruk Adie; Temesgen, Mamaru Mollalign (Frontiers in Medicine, 2023)
Background: Anemia is the most prevalent public health burden during pregnancy. Severe maternal and fetal complications have been associated with anemia. Despite the different efforts made, the high prevalence of preoperative anemia, combined with increasing global rates of cesarean section, is a significant global health issue. Objective: This study was conducted to determine the prevalence and associated factors of preoperative anemia in parturients undergoing cesarean section at a comprehensive specialized hospital in Ethiopia. Methods: An institution-based cross-sectional study was conducted to determine preoperative anemia from April to June 2022. The study included a total of 424 parturient mothers undergoing cesarean section. Data were obtained using a standardized questionnaire that included parturients' background characteristics. Bi-variable and multi-variable logistic regression analyses were performed to identify variables related to preoperative anemia. With a 95% confidence level, the estimated crude odds ratio and adjusted odds ratio were calculated. In a multivariate analysis, variables were considered statistically significant if their p-value was less than 0.05. Result: The prevalence of preoperative maternal anemia was 28.3% (95% CI: 23.8%-32.5%). previous history of abortion, lack of iron supplementation, HIV infection, previous cesarean sections and ASA physical status III were significantly associated with preoperative anemia in parturients. Conclusion: The overall prevalence of preoperative anemia among parturients who underwent cesarean section was significant. Lack of Iron supplementation, ASA III, previous history of abortion, HIV infection, and previous cesarean section were associated with anemia. Identification of high-risk parturients and prevention of preoperative anemia is essential.